RANTES/CCL5 Induces Collagen Degradation by Activating MMP-1 and MMP-13 Expression in Human Rheumatoid Arthritis Synovial Fibroblasts - Agere, Solomon A.; Akhtar, Nahid; Watson, Jeffery M.; Ahmed, Salahuddin (Frontiers in Immunology, 2017)
RANTES/CCL5 participates in rheumatoid arthritis (RA) pathogenesis by facilitating leukocyte infiltration, however, its other pathological functions are not fully defined in RA. In the present study, we evaluated the effect of RANTES/CCL5 on tissue degrading enzymes matrix metalloproteinase-1 (MMP-1) and MMP-13 expression and its contribution to the progressive joint damage by RA synovial fibroblasts (RASFs). Our results showed that RANTES/CCL5 dose-dependently induced MMP-1 and MMP-13 expression in monolayers and three-dimentional (3D) micromass of human RASFs, which correlated with an increase in collagenase activity. This activation by RANTES/CCL5 was observed in RASF, but not in osteoarthritis SFs (OASFs). Evaluation of the signaling events showed that RANTES/CCL5 selectively activated PKCδ, JNK, and ERK proteins to induce MMP expression in human RASFs. Pretreatment with a functional antagonist (Met-RANTES) or heparinase III (an enzyme that selectively digests heparan sulfate proteoglycans, HSPGs) completely abrogated RANTES/CCL5-induced MMP-1 and MMP-13 expression. Interestingly, the inhibition of RANTES/CCL5 using small interfering RNA (siRNA) approach reduced the ability of IL-1β to induce MMP-1 and MMP-13 expression, asserting its mediatory role in tissue remodeling. In the inhibitor study, only the selective inhibition of HSPGs or PKCδ, ERK, and JNK markedly inhibited RANTES/CCL5-induced MMP-1 and MMP-13 production. Circular dichroism (CD) spectroscopy results demonstrated the degradation of collagen triple-helical structure upon exposure to the conditioned media from RANTES/CCL5 stimulated RASFs, which was reverted by a broad-spectrum MMP inhibitor (GM6001). These findings suggest that RANTES/CCL5 not only up-regulates MMP-1 and MMP-13 expression by utilizing HSPGs and/or PKCδ-JNK/ERK pathways, but also mediates IL-1β-induced MMP-1 and MMP-13 expression.